Empirical model of the cooling liquid steel spoon 15TM: an industrial perspective - Mancha Gonzales, Salvatore (2012)
It seeks to develop a mathematical model that predicts the decay of the temperature of the liquid steel spoon 15 TM. The shots were made in temperature castings production, measuring the temperature after excoriated and before emptying the holding furnace, the time was also recorded between the two jacks temperature. Then the data obtained was analyzed to obtain the parameters of the particular model (K and T0). The derivation of the model was obtained from an Ordinary Differential Equation (ODE) homogeneous. Prognostic value of the model obtained with new values ​​measured temperature was compared. To make the prognosis of two different values ​​of temperature T0, one with a constant value of T0, as shown in the model found, and another with T0, a variable that was numerically equal to the temperature after excoriated were used, both forecasts were compared with various indicators. Which influence the value T0 in the model is determined. Stability parameter K by t-student test for the two sets of data was evaluated and finally the total error of temperature measurement considering the forecast error and the error of the equipment used is estimated.